Analysis of volatile compounds in Annona squamosa L. fruit under cold storage based on HS-GC-IMS. Issue 3 (February 2020) - Gong, Xiao; Tan, Ge; Hu, Xiaojun; Li, Jihua
Abstract: Annona squamosa L., also known as sugar apple, sweetsop, is listed as one of the world's five largest tropical fruits and is commercially cultivated in tropical and subtropical regions of China. To analyze the effect of different preservatives on the volatile aroma components of sugar beets during cold storage, the samples were stored at 4 °C and sampled every two days. The change in volatile aroma components was studied by changing the composition of the preservative. The volatile aroma components in the storage of sweetsop were analyzed by GC-IMS. The results indicated that the preservation of the sweetsop by 1-MCP made the volatile aroma as much as possible with the fresh components under the condition of cold storage. The findings of this study are of great significance for the research and development of the future preservation method of Annona squamosa L. fruit and will provide theoretical support for the preservation technology of tropical fruits.